Problem-solving step analysis for increasing tire static balance levels: a case study - Febriana, Tubagus Hendri; Herlambang, Hendi; Hernadewita, Hernadewita; Hasbullah, Hasbullah; Halim, Abdul (Universitas Serang Raya, 2021)
One of the company's efforts in implementing the commitment to customer satisfaction is carried out through continuous improvement activities. All indicators are evaluated to determine the level of quality stability against process variations that will impact non-compliance with predetermined product specifications. One of the quality problems found in the tire manufacture industry is the out-percentage of tire uniformity, which suddenly increases, one of which is the value of static balance. This study analyses the process variation factors that occur to take corrective and preventive actions through a series of Root Cause Analysis (RCA), Fault Tree Analysis (FTA), and Failure Mode and Effect Analysis (FMEA). Refers to the analysis result, it was found that there was a problem with the rubber film gauge variation at the manufacturing step of the steel breaker, one of the material components in the tire construction. Two main factors cause rubber film thickness variation: rubber sticky with roll calendar, Radial Run Out (RRO) Roll Calendar out standard, and viscosity compound variation with 12 root problems found. The results of the improvements that have been made can effectively improve rubber film thickness variation, increase the Cpk level of steel breaker material from 0.82 to 1.91 and reduce the out percentage ratio of static balance by 54.65%.